2019
DOI: 10.1021/acsami.9b21531
|View full text |Cite
|
Sign up to set email alerts
|

Organic/Inorganic Hybrid Buffer in InGaZnO Transistors under Repetitive Bending Stress for High Electrical and Mechanical Stability

Abstract: We investigated the influence of the multilayered hybrid buffer consisting of Al2O3/PA (polyacrylic) organic layer/Al2O3 on the electrical and mechanical properties of amorphous InGaZnO (a-IGZO) thin-film transistors (TFTs). The multilayered organic/inorganic hybrid buffer has multiple beneficial effects on the flexible TFTs under repetitive bending stress. First, compared to the PA or Al2O3 single-layered buffer, the multilayered hybrid buffer showed an improved WVTR value of 1.1 × 10–4 g/m2 day. Even after 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…16 The well-known sensitivity of a-IGZO to atmospheric effects is known to contribute to device instability and is a major attraction of top-gate devices. 37,48,66 Numerous studies have reported improved environmental stability of top-gate a-IGZO TFTs using a variety of dielectric materials. 41,43,60,69 It is therefore expected that the top-gate SAND TFTs will have superior environmental stability compared to bottom-gate devices.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…16 The well-known sensitivity of a-IGZO to atmospheric effects is known to contribute to device instability and is a major attraction of top-gate devices. 37,48,66 Numerous studies have reported improved environmental stability of top-gate a-IGZO TFTs using a variety of dielectric materials. 41,43,60,69 It is therefore expected that the top-gate SAND TFTs will have superior environmental stability compared to bottom-gate devices.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[ 21,22 ] Also, adopting an organic/inorganic hybrid buffer layer in a top‐gate a‐IGZO TFT has shown improved mechanical stability by changing the stress distribution in the device. [ 23 ] In addition, adopting more flexible carbon‐based materials for a‐IGZO TFT‐based amplifiers on an ultrathin (<3 µm) PI substrate also allowed the demonstration of flexible metal‐oxide/carbon nanotube complementary circuits with reliable electrical and mechanical characteristics. [ 24 ]…”
Section: Figurementioning
confidence: 99%
“…Although flexible electronic is achieving a great variety of applications, [ 1–4 ] most of them were suffered from the device performance degradation caused by bending over time. [ 5–7 ] This issue was related to bending can result in the generation of cracks. [ 8 – 10 ]…”
Section: Introductionmentioning
confidence: 99%